For every 50 emails that Nick sent in a month, he received 30 emails. What is the ratio in simplest form of the number of emails sent to the number of emails received by Nick that month?
The ratio of emails sent to emails received by Nick that month is 5:3 in its simplest form, determined by calculating their greatest common divisor.
Explanation:The subject of your question is ratios and it falls under the category of Mathematics.
'For every 50 emails that Nick sent in a month, he received 30 emails.' This tells us about a ratio. A ratio is a way to compare amounts of something.
The ratio in this case is the number of emails sent by Nick to the number of emails he received. We express this ratio as '50:30'.
To simplify the ratio, we find the greatest common divisor (GCD) of 50 and 30, which is 10. So, we divide both numbers by 10. Thus, our simplified ratio is 5:3.
This means Nick sent 5 emails for every 3 emails he received, in simplest terms.
Learn more about Ratios here:https://brainly.com/question/32531170
#SPJ3
A movie rental club charges $4.95 for membership and $18.95 for each month of subscription. If the first month were free, what would be the cost of a yearly membership?
4.95+(18.95 x 11) = $213.40 a year
A grocery store has 184 shelves for bottled goods. Each shelf can hold 27 bottles. How many bottles will the shelves hold in all?
Each shelve will hold 7 bottles.
they can hold 4,968 bottles
A theater can seat 120 people. The number of rows is 7 less than the number of seats in each row. How many rows of seats are there?
Let x be the number of rows.
If the number of rows is 7 less than the number of seats in each row, then the number of seats in a row is x+7. The total number of seats is
x·(x+7).
You know that a theater can seat 120 people, then
x·(x+7)=120.
Solve it:
[tex]x^2+7x-120=0,\\\\D=7^2-4\cdot (-120)=49+480=529,\ \sqrt{D}=23,\\\\x_1=\dfrac{-7+23}{2}=8, \ x_2=\dfrac{-7-23}{2}=-15.[/tex]
The number of rows must be positive, then x=8.
Answer: there are 8 rows with 15 seats at each.
There is an animal farm where chickens and cows live. All together, there are 82 heads and 192 legs. How many chickens and cows are there on the farm?
Answer:
There are 14 cows and 68 Chicken in the farm.
Step-by-step explanation:
A Cow has 4 legs
Chicken has 2 legs.
Lets take there [tex]x[/tex] chickens AND,
there are [tex]y[/tex] number of Cows.
Now we can write two equations for the number of heads and legs.
For the number of heads we can write,
[tex]x+y=82[/tex] <--------- 1st equation
For the number of legs we can write,
[tex]2x+4y=192[/tex] <------ 2nd equation
We can now solve the simultaneous equations to find [tex]x[/tex] and [tex]y[/tex]
Multiply 1st equation by 2 and deduct it from 2nd equation to remove [tex]x[/tex]
⇒[tex]2x+4y-2*(x+y)=192-164[/tex]
⇒[tex]2x+4y-2x-2y)=112-164[/tex]
⇒[tex]2y=28[/tex]
⇒[tex]y=14[/tex]
Therefore, there are 14 cows in the farm.
Now we can substitute the [tex]y[/tex] value to the 1st equation and find [tex]x[/tex] value.
[tex]x+14=82[/tex]
[tex]x=68[/tex]
Therefore, there are 68 chickens in the farm.
True or false? If you look a true “if then” statement, inserted a not in each clause, and reversed the clauses, the new statement would also be true.
True becauseIf you look a true “if then” statement, inserted a not in each clause, and reversed the clauses, the new statement would also be true.
Answer:
It's true
Step-by-step explanation:
5.6 Show your work
x 7.3
———
Hello there!
[tex]5.6*7.3[/tex]
Explanation:
↓↓↓↓↓↓↓↓
First you had to multiply without the decimal points, and then you put the decimal point it should be the correct answer.
[tex]56*73=4088[/tex]
5.6 it has one decimal place.
7.3 it has one decimal place.
Therefore, the answer should be the two decimal places.
[tex]=40.88[/tex]
Answer⇒⇒⇒⇒⇒40.88
Hope this helps!
Thank you for posting your question at here on Brainly.
Have a great day!
-Charlie
Find the perimeter of the triangle.
The base is from 2 to 7, which is 5 units long.
The height is from 1 to 8, which is 7 units tall.
Using the Pythagorean theorem we can calculate the hypotenuse:
Hypotenuse = √5^2 +7^2=
√25 +49=
√74=
8.6
Perimeter = 5 + 7 + 8.6 = 20.6
The answer is C.
two angles are supplementary if the sum of their measures is 180°. If one of two supplementary angles measures 85°, what is the measure of the other angle?
95° because 85 + x = 180 so you do 180 - 85 and get 95
Jones of Boston borrowed $40,000, on a 90-day 10% note. After 60 days, Jones made an initial payment of $6,000. On day 80, Jones made an additional payment of $7,000. Assuming the U.S. Rule, what's the adjusted balance of the first payment? (Use 360 days.)
Answer:
$34,666.67
Step-by-step explanation:
Step 1: Calculate the interest for 60 days.
(40000*60/360 )* 0.10 = $666.67
Step 2: Amount = Principal + Interest = $40,000 + 666.67 = $40,666.67
Step 3 : After 60 days, he paid $6000.
Remaining balance of the first payment = 40666.67 - 6000 = $34,666.67
Thank you.
There is a "buy 3 get 1 free" sign for candy bars at the store. Each candy bar cost $0.50. What os the price of 12 candy bars?
$4.50 because 3 were free wich means 9 cost money 9*0.50=4.5
The cost of 12 candy bars with a 'buy 3 get 1 free' offer is $4.50.
Explanation:To calculate the cost of 12 candy bars under the 'buy 3 get 1 free' deal, we need to divide the 12 by the group size, which is 4 (3 that you pay for + 1 that you get for free). This results in 3 groups. Since you only pay for 3 candy bars in each group, each group will cost you $0.50 x 3 = $1.50. So, the total cost for 12 candy bars is $1.50 x 3 = $4.50.
Learn more about Calculations for discounts here:https://brainly.com/question/32761587
#SPJ12
Help me to answer now ineed this
Please...
Simplify -3[5 - (-8 + 6)]
First, solve the parenthesis
-8 + 6 = -2
-3[5 - (-2)]
Note that two negatives = one positive
-3[5 - (-2)] = -3[5 + 2]
Simplify. Solve the bracket
-3[5 + 2] = -3[8]
Simplify. Multiply to get the answer
-3 x 8 = -24
-24 is your answer
hope this helps
Answer:
-21
#RoadToGraduation
Step-by-step explanation:
Which phrase correctly orders –23, 11, –17, and 5?
A.
–17 < –23 < 5 < 11
B.
–23 < –17 < 5 < 11
C.
5 < 11 < –17 < –23
D.
–23 < 11 < –17 < 5
P=a+b-4 you have to solve for a
P = a + b - 4
subtract b from both sides
P - b = a - 4
add 4 to both sides
P - b + 4 = a
To solve for 'a' in the equation P = a + b - 4, you should subtract 'b' from both sides and add 4 to both sides to get a = P - b + 4.
Explanation:The question asks to solve for a in the equation P = a + b - 4. To do this, we need to isolate a on one side of the equation. Thus, we start by subtracting b from both sides and then adding 4 to both sides. The resulting equation will be a = P - b + 4. This procedure is quite different than solving quadratic equations like ax² + bx + c = 0, where we have to use the quadratic formula -b ± √b² - 4ac / 2a to find the solutions.
Learn more about Solving Linear Equations:https://brainly.com/question/18322830
#SPJ11
Solve the equation 4c^2+7c-5=0 using the quadratic formula.
[tex]c = \frac{-7+\sqrt{129} }{8} ,\frac{-77-\sqrt{129} }{8}[/tex]
The result of multiplying two or more numbers is a____
The answer is: Product.
The explanation for this completion exercise is shown below:
By definition, a product is the result of multiply two or more factors. For example:
[tex](6)(2)=12[/tex] (The factors are 6 (Multiplier) and 2 (Multiplicand) and the result or the product is 12).
[tex](10)(8)=80[/tex] ( (The factors are 10 (Multiplier) and 8 (Multiplicand) and the result or the product is 80).
Simplify: x+2/x^2-6x-16 ÷ 1/9x
Answer:
Step-by-step explanation:
Two jets leave an air base at the same time and travel in opposite directions. One jet travels 60 /mih faster than the other. If the two jets are 7848mi apart after 6 hours, what is the rate of each jet?
The speed of the slower jets and faster jets are 624 mi / Hr and 684 mi/hr respectively.
What is speed?Speed is defined as the ratio of the time distance travelled by the body to the time taken by the body to cover the distance.
Let the speed of a slower jet be represented as 'x'
Now Given:
one jet travels 60 mph slower than the other.
Hence Speed of a faster jet will be = x + 60
Distance = 7848 miles
Time = 6 hrs
Now we know that;
Distance is equal to the product of speed and time.
Framing in the equation we get;
Distance = (Speed of Faster Jet + Speed of Slower jet) × Time.
Substituting the given values we get;
7848 = ( x + x + 60 ) 6
7848 = 12x + 360
x = 624
Speed of slower jet = 624 miles/hr
Speed of faster jet = 624 + 60 = 684 miles/hr
Hence Speed of the Faster jet is 684 miles/hr and the speed of the slower jet is 624 miles/hr.
To know more about Speed follow
https://brainly.com/question/6504879
#SPJ2
plsss answer , thank youuuu
Hi
The answer is
A) The term 8f represents the cost of f stems of flowers at $8 per stem.
Thank you.
For this case we have the following expression:
[tex]13v + 8f + 6b + 3m\\[/tex]
That represents the total cost, in dollars, of the silk floral arrangements.
The variables are the following:
v: number of vases
f: amount of stems of flowers
b: quantity of stems of wood bark
m: number of packages of marbles
Thus, 8f Represents the cost associated with the quantity of stems of flowers, where f represents that amount
Answer:
option A
Find the value of a if x=3 is a solution to the equation x/a=7
im confused, picture up above
Answer:
Its Option B
Step-by-step explanation:
Total Amount of Ice Cream = 2/3 cup
Ice Cream Taken = Two Scoops of 1/6 cups = 2 x 1/6 = 2/6
Ice Cream Left = Total Amount of Ice Cream - Ice Cream Taken
= 2/3 - 2/6
= 2/6
Hope That explains it!
Brainliest?
Solve the equation using addition or subtraction.
4=q+13
A q=4
B q=17
C q=-9
D q=-2
Solve the equation using addition or subtraction.
5.5= -2+d
A d=5
B d=7.5
C d=5.5
D d=3.5
Solve the equation using multiplication or division
-7y=28
A y= -4
B y=4
C y=14
D y=35
Solve the equation using multiplication or division
-13 = m/ -5
A m=13/5
B m=45
C m=65
D m= 5/13
Answer:
1. Solve the equation using addition or subtraction.
[tex]4=q+13[/tex]
Taking like terms on one side, we get
[tex]4-13=q[/tex]
=> [tex]-9=q[/tex]
or [tex]q=-9[/tex] (option C)
2. Solve the equation using addition or subtraction.
[tex]5.5= -2+d[/tex]
Taking like terms on one side, we get
[tex]5.5+2=d[/tex]
So, [tex]d=7.5[/tex] (option B)
3. Solve the equation using multiplication or division
[tex]-7y=28[/tex]
Dividing both sides by 7, we get
[tex]-y=4[/tex]
or [tex]y=-4[/tex] (option A)
4. Solve the equation using multiplication or division
[tex]-13=\frac{m}{-5}[/tex]
Cross multiplying -13 and -5 to get the value of m
[tex]m=(-13)(-5)[/tex]
[tex]m= 65[/tex] (option C)
The solutions of the equations are =
1) C) q = -9.
2) B) d = 7.5.
3) A) y = -4.
4) C) m = 65.
Given are the equation we need to solve them,
Let's solve the equations one by one:
1) 4 = q + 13
To isolate q, we can subtract 13 from both sides of the equation:
4 - 13 = q + 13 - 13
-9 = q
Therefore, q = -9.
The correct answer is C) q = -9.
2)5.5 = -2 + d
To isolate d, we can subtract -2 from both sides of the equation:
5.5 - (-2) = -2 + d - (-2)
5.5 + 2 = d
7.5 = d
Therefore, d = 7.5.
The correct answer is B) d = 7.5.
3) -7y = 28
To solve for y, we can divide both sides of the equation by -7:
(-7y) / (-7) = 28 / (-7)
y = -4
Therefore, y = -4.
The correct answer is A) y = -4.
4) -13 = m / -5
To isolate m, we can multiply both sides of the equation by -5:
-5 x (-13) = m
65 = m
Therefore, m = 65.
The correct answer is C) m = 65.
Learn more about Equations click;
https://brainly.com/question/29538993
#SPJ6
Help me please that’s easy but....
Let's resolve the powers of 10 to make them comparable
47000
45000
5000
280000
125000
Now you can see the largest is 280000 and the smallest is 5000
Their difference is 280000 - 5000 = 275000
A surplus is
When you spend more than you have in income
When you spend less than you have in income
When you spend the same amount that you have in income
Another word for income
A surplus is "When you spend less than you have in income".
What is income?Income is the monetary value that a person earns against a service or a business.
When the person spends less than his income or spends less than the expected expenditure, then the extra saved money is known as a surplus.
Hence, A surplus is "When you spend less than you have in income".
Learn more about income here:
https://brainly.com/question/14732695
#SPJ2
Round the sum of 43.524 +3.004 to the nearest tenth
Answer:
46.50
I hope this helped
43.524 +3.004= 46.528
rounded you should get 46.530
sorry if i couldnt help hope i did! :)
the length of a rectangular swimming pool is triple its width the pool covers an area of 192 m squared
To find the dimensions of the rectangular swimming pool, we can use the formula for the area of a rectangle. The width is 8 meters and the length is 24 meters.
Explanation:To find the dimensions of the rectangular swimming pool, let's assume the width to be 'w' meters. According to the given information, the length of the pool is triple the width, which means the length is 3w meters. To find the area of the pool, we can use the formula: Area = Length × Width.
Given that the area of the pool is 192 m², we can substitute the values into the formula as follows:
192 = (3w) × w
192 = 3w²
Dividing both sides of the equation by 3, we get:
w² = 64
Taking the square root of both sides of the equation, we get:
w = ±8
Since the width cannot be negative, the width of the pool is 8 meters. The length of the pool can be calculated by multiplying the width by 3:
Length = 3 × 8 = 24 meters
Therefore, the dimensions of the rectangular swimming pool are 8 meters by 24 meters.
A batch of cookies for 3/4 cup of flour.You want to make 1/2 of a batch.How much flour do you need?
First will make the fraction is easier by turning it into 6/8 but because we’re halving it the we only halve the numerator, so it’s 3/8.
If this can’t be understood I’d gladly help elaborate
NEED HELP IMMEDIATELY Which expression is equivalent to one over four n − 16? a. one over four(n − 4)
b. one over four(n − 64)
c. 4(n − 4)
d. 4(n − 64)
A because just multiply 1/4 by 16 and u get 4
If f(x)= 2x^2 -3x+1, find f(3)-f(2).
A. 0
B. 7
C. 17
and briefly explain pleaseee
f(3) = 2x² - 3x + 1
2(3)² - 3(3) + 1
18 - 9 + 1
F(3) = 10
f(2) = 2(2)² - 3(2) + 1
8 - 6 + 1
f(2) = 3
f(3) - f(2)
10 - 3
f(3) - f(2) = 7 because you find f(3) = 10, and f(2) = 3, and plug in the answer you found. This gives you 10 - 3, which is 7.
The value of f(3) - f(2) is 7 if the function f(x) = 2x² - 3x + 1 the correct answer is option B: 7.
To find f(3) and f(2), we need to plug the respective values of x into the given function f(x) = 2x² - 3x + 1 and then subtract the results.
f(3):
f(3) = 2(3)² - 3(3) + 1
f(3) = 2(9) - 9 + 1
f(3) = 18 - 9 + 1
f(3) = 10
f(2):
f(2) = 2(2)² - 3(2) + 1
f(2) = 2(4) - 6 + 1
f(2) = 8 - 6 + 1
f(2) = 3
Now, let's find f(3) - f(2):
f(3) - f(2) = 10 - 3 = 7
So, the value of f(3) - f(2) is 7.
The correct answer is option B: 7.
To know more about function click here :
https://brainly.com/question/34734445
#SPJ2